Summary of experiences and studies for wind integration: IEA Wind Task 25 - Holttinen, Hannele (2014)
IEA WIND R&D Task 25 on “Design and Operation of Power Systems with Large Amounts of Wind Power” collects and shares information on wind generation impacts on power systems, with analyses and guidelines on methodologies. This paper summarizes the main results from the report published on January 2013 describing experience of wind integration as well as the most relevant wind power grid integration studies in the 15 participating countries. The studies build on the already significant experience in integrating wind power in power systems addressing concerns about the impact of wind power’s variability and uncertainty on power system security of supply and costs as well as grid reinforcement needs. The mitigation of wind power impacts includes more flexible operational methods, incentivising flexibility in other generating plants, increasing interconnection to neighbouring regions, and application of demand-side flexibility. Electricity storage is still not as cost effective in larger power systems as other means of flexibility, but is already seeing initial applications in places with limited transmission.